Early growth and neurodevelopmental outcome in very preterm infants: impact of gender. Issue 5 (10th June 2014) - Frondas-Chauty, A; Simon, L; Branger, B; Gascoin, G; Flamant, C; Ancel, P Y; Darmaun, D; Rozé, J C
Abstract : Background and objective: Nutrition in the neonatal unit may impact the neurological outcome of very preterm infants, and male preterms are more likely to suffer neonatal morbidity and adverse neurological outcomes. We hypothesised that growth during hospitalisation would impact neurological outcome differently, depending on infant gender. Methods: Surviving infants born between 1 January 2003 and 31 December 2009 with a gestational age <33 weeks, and enrolled in Loire Infant Follow-up Team, a regional cohort in western France, qualified for the study. Growth during neonatal hospitalisation was assessed by the change in weight z-score between birth and discharge, and infants where ranked into 5 classes, depending on their change in z-score (<−2, −2 to −1.01, −1 to −0.51, −0.50 to 0.01 and ≥0), the last class being the reference. The main outcome criterion was neurodevelopmental outcome at 2 years of corrected age. For each class of changes in weight z-score, crude or adjusted OR for non-optimal outcome was calculated for each gender, and compared between genders. Results: 1221 boys and 1056 girls were included. Gender and early growth interact, (p=0.02). Moreover when change in weight z-score varied from <−2 to (−0.50 to −0.01), adjusted OR for non-optimal outcome varied from 3.2 (1.5–6.8) to 2.2 (1.2–4.1) in boys versus 1.8 (0.7–4.2) to 0.95 (0.4–1.9) in girls. For each class, the OR was significantly higher in boys. Conclusions: In very preterm infants, male neurodevelopment appears to be much more sensitive than female to poor postnatal growth.